Judicial review - Rusu, Mihaela (Eximia, 2023)
Individual freedom, together with the security of the person, are values to which the fundamental law of the State grants a character of inviolability. This recognition of the significance of value has led to the establishment in the Constitution of general points in which one can deviate from the principle of inviolability of freedom: nature of preventive measure, duration, competent judicial body. The constitutional principle stated is known at the level of law in Article 5 of the European Convention on Human Rights, in order to ensure a uniform level of interpretation of the legal norms regarding any restriction of the freedom of the individual. The right to liberty – as proclaimed in Article 5 of the Convention concerns, of course, the physical freedom of the person, and the stated purpose of protection is to ensure that no human being can be deprived of this right. Despite these views, the post-December criminal procedure legislation has failed to harmonise with the European spirit nor to fully satisfy the principles resulting from the case-law of the Strasbourg Court. It took a major legislative invention to bring back to normality the provisions contained in the Criminal Procedure Code and the enforcement laws and to show that Romania respects its arrogant international obligations in the field of criminal procedure law. The legislator itself noted, in justifying the revision of the legal norms (substantive and procedural), that the amendments aimed to ensure a unitary protection of the freedoms guaranteed by the Constitution and international legal instruments, to streamline the criminal process and, at the same time, the fair conduct of judicial proceedings for all participants in the criminal process. As a method of governing state power, coercion has priority, conviction having an auxiliary role, but it is ubiquitous. Any state-organized society has a coercive force, varying only the forms of coercion, its intensity, and the relations between coercion and conviction.